2009
DOI: 10.1086/596617
|View full text |Cite
|
Sign up to set email alerts
|

Investments, Time Preferences, and Public Transfers Paid to Women

Abstract: The literature suggests men and women may have different preferences. This paper exploits a social experiment in which women in treatment households were given a large public cash transfer (PROGRESA). In an effort to disentangle the effect of additional income in the household from the effect of changing the distribution of income within the household, the impact of PROGRESA income on savings and investments decisions is compared with all other income sources (after taking into account participation in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 30 publications
5
97
0
1
Order By: Relevance
“…However, the interesting finding is that within these same programmes, food and total consumption were found to increase by equivalent proportions. Other studies, for which we were not able to estimate effect sizes, also found that both total and food consumption increased as a result of the transfer including in Nicaragua (Maluccio, 2007;Gitter and Caldes, 2010) as well as urban (Angelucci and Attanasio, 2006) and rural Mexico (Rubalcava et al 2009). …”
Section: Impacts On Consumption Investment and Savingsmentioning
confidence: 62%
See 2 more Smart Citations
“…However, the interesting finding is that within these same programmes, food and total consumption were found to increase by equivalent proportions. Other studies, for which we were not able to estimate effect sizes, also found that both total and food consumption increased as a result of the transfer including in Nicaragua (Maluccio, 2007;Gitter and Caldes, 2010) as well as urban (Angelucci and Attanasio, 2006) and rural Mexico (Rubalcava et al 2009). …”
Section: Impacts On Consumption Investment and Savingsmentioning
confidence: 62%
“…Mexico, transfers to women in couple headed households resulted in higher quality nutritional intake, purchases of children's clothing and female associated forms of investment, but not in households headed by a single parent, whether male or female (Rubalcava et al 2009). The proportion of the transfer income consumed was estimated between 80 and 90 percent in Brazil (Resende and Oliveira, 2008), Colombia (Angelucci and Attanasio, 2006) and Mexico (Gertler et al 2006).…”
Section: Impacts On Consumption Investment and Savingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rubalcava, Teruel, and Thomas (2004) show that the additional resources to the families from PROGRESA are spent on children's goods, better nutrition and investments in small livestock (traditionally managed by women in Mexico).…”
Section: Related Literaturementioning
confidence: 99%
“…Numerous studies document that income or assets accruing to women or believed to be controlled by women are more likely than those of men to be allocated to expenditure that benefit children (e.g., education) as well as themselves, such as food and health care (e.g., Haddad et al (1997); Duflo (2003); Quisumbing and Maluccio (2003); Smith (2003); Rubalcava et al (2009); LaFave and Thomas (2017)). We rely on the collective households framework (Chiappori (1988(Chiappori ( , 1992) which uses household consumption data to structurally estimate a measure of women's empowerment.…”
Section: Introductionmentioning
confidence: 99%